CHANGES OF THERMOCLINE DEPTH AT THE SUMBA ISLAND OFFSHORE BASED ON PLANKTONIC FORAMINIFERAL ASSEMBLAGES AND ITS IMPLICATION TO EUTROPHICATION SINCE THE LAST DEGLACIATION (~18 ka BP): A PRELIMINARY STUDY - Ryan Dwi Wahyu Ardi; Aswan Aswan; Khoiril Anwar Maryunani; Eko Yulianto; Purna Sulastya Putra; Septriono Hari Nugroho (Rudarsko-geološko-naftni Zbornik, 2021)
Changes of the thermocline depth (DOT) at the Sumba Island offshore are not well-known compared to the DOT changes in the Timor Sea, the main exit passage of the Indonesian Through-flow (ITF). Planktonic foraminiferal assemblages in cores collected from the southwest Sumba offshore (ST08) and Sumba Strait (ST12, ST13, and ST14) were used as a tool to infer the DOT and paleoproductivity changes at the Sumba Island offshore. The DOT changes were indicated from the thermocline and mixed layer dwellers’ relative abundance while the paleoproductivity changes were indicated from the relative abundance of Neogloboquadrina dutertrei. This study suggests a contrast between the DOT pattern at the Sumba Island offshore and the DOT pattern in the Timor Sea during the Last Deglaciation–Holocene. The contrast DOT pattern indicated that the multi-millennial changes of the Australian-Indonesian monsoon (AIM) during the Last Deglaciation– Holocene were the main factors behind the DOT changes in this region while the effects of El Niño Southern Oscillation (ENSO) –like, Indian Ocean Dipole (IOD) –like, and ITF to DOT changes were minimal. Paleoproductivity enhancement at the Sumba Island offshore was not solely related to the monsoon-driven coastal upwelling intensification, which resulted in the DOT shoaling and eutrophic condition. The increase of nutrient availability in surface water due to river runoff increase and changes in the lifted water mass nature were also able to enhance productivity in this region.